Validation of the Spiritual Distress Scale in Portuguese cancer patients undergoing chemotherapy: a methodological study - Martins, Helga (2019)
Spiritual distress may ascend from unmet spiritual needs. The use of instruments to measure spiritual distress seems to facilitate the approach to spirituality, such as the Spiritual Distress Scale (SDS) that has been used worldwide. No instrument to assess spiritual distress in cancer patients is currently available in Portugal. This study aims to conduct the translation, adaptation and validation of the SDS in Portuguese cancer patients undergoing chemotherapy. Methodological study based on Sousa and Rojjanasrirat (2011), a seven-step approach, started with the linguistic translation to the psychometric tests. The main participants (55.4%) were older than 60 years; about 64.7% were females, married (68.0%), and 86.7% were Catholic. Moderate spiritual distress was experienced by 49.3% of the participants. Linguistic and conceptual equivalences were obtained. The SDS European Portuguese version has an overall Cronbach’s alpha of 0.91, and the subscales were as follows: “relationship with self” (0.92), “relationship with others” (0.63), “relationship with God” (0.64) and “facing death” (0.85). Four factors emerged after Varimax rotation. Overall, these results indicate that the SDS European Portuguese version has good psychometric characteristics and can used in assessing spiritual distress in cancer patients.